A COMPARATIVE ANALYSIS OF GENDER-SPECIFIC LEXICON IN ENGLISH, RUSSIAN, AND UZBEK LANGUAGES (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article is dedicated to the comparative analysis of gender lexicons in Uzbek, Russian, and English languages.